Photoplethysmography based remote health monitoring system - Harbawi, Malek A.; Ibrahimy, Muhammad Ibn; Motakabber, S. M. A. (2013)
One of the world's most leading killer diseases is the cardiovascular disease, which accounts for 16.7 million deaths annually. Out of the total population in the world, about 22 million people run the risk of sudden heart failure. However, saving the lives of cardiac patients can be improved by the emergency monitoring so that the initiation of treatment can be taken up within the crucial hour. The acquired signals by pulse oximetry provide significant information about the heart-rate, arterial blood oxygenation, blood pressure and respiratory-rate. Telemedicine provides a great impact in the emergency monitoring of patients located in remote nonclinical environments. A home cardiac telemedicine emergency system based on photoplethysmography has been developed. The acquired signals are processed, transmitted and stored in a local PC. Finally, the data are sent to the remote terminal located at the hospital through internet. The diagnoses are done by specialists from the reading and action can be immediately taken in emergency cases.